Development of Molecular Mechanisms and Their Application on Oncolytic Newcastle Disease Virus in Cancer Therapy - Huang, Fang; Dai, Chuanjing; Zhang, Youni; Zhao, Yuqi; Wang, Yigang; Ru, Guoqing (Frontiers in Molecular Biosciences, 2022)
Cancer is caused by the destruction or mutation of cellular genetic materials induced by environmental or genetic factors. It is defined by uncontrolled cell proliferation and abnormality of the apoptotic pathways. The majority of human malignancies are characterized by distant metastasis and dissemination. Currently, the most common means of cancer treatment include surgery, radiotherapy, and chemotherapy, which usually damage healthy cells and cause toxicity in patients. Targeted therapy is an effective tumor treatment method with few side effects. At present, some targeted therapeutic drugs have achieved encouraging results in clinical studies, but how to improve the targeting and the delivery efficiency of these drugs remains a challenge. In recent years, oncolytic virus (OV) has been used to direct the tumor-targeted therapy or immunotherapy. Newcastle disease virus (NDV) is a solid oncolytic agent capable of directly killing tumor cells and increasing tumor antigen exposure. Simultaneously, NDV can trigger the proliferation of tumor-specific immune cells and thus improve the therapeutic efficacy of NDV in cancer. Based on NDV's inherent oncolytic activity and the stimulation of anti-tumor immune responses, the combination of NDV and other tumor therapy approaches can improve anti-tumor efficacy while reducing drug toxicity, indicating a broad application potential. We discuss the biological properties of NDV, the anti-tumor molecular mechanisms of oncolytic NDV, and its application in the field of tumor therapy in this review. Furthermore, we presented new insights into the challenges that NDV will confront and suggestions for increasing NDV's therapeutic efficacy in cancer.